2009
DOI: 10.1212/wnl.0b013e3181b23551
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological status at seizure onset in children

Abstract: Objective: This large, prospective, community-based study characterized neuropsychological functioning and academic achievement at the time of the first recognized seizure and identified risk factors for cognitive deficits. Methods:We compared 282 children (ages 6 -14 years, IQ Ն70) with a first recognized seizure to 147 healthy siblings on a battery of well-standardized and widely used neuropsychological and academic achievement tests and examined relationships with demographic and clinical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
165
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(181 citation statements)
references
References 43 publications
6
165
4
6
Order By: Relevance
“…This finding is consistent with the literature that shows that ongoing refractory seizures are associated with poorer cognitive outcome. 5,9,24 In contrast, the patients with short duration of seizures prior to resection had better outcomes, with more postsurgical improvement. These findings argue for earlier resection in the context of lesion-associated seizures to preserve cognitive functions.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is consistent with the literature that shows that ongoing refractory seizures are associated with poorer cognitive outcome. 5,9,24 In contrast, the patients with short duration of seizures prior to resection had better outcomes, with more postsurgical improvement. These findings argue for earlier resection in the context of lesion-associated seizures to preserve cognitive functions.…”
Section: Discussionmentioning
confidence: 94%
“…The other investigators explained that the cognitive impairment could be attributed to brain damage, age of onset of epilepsy, nature and location of seizure focus, duration of epilepsy, anticonvulsant drugs and epilepsy related surgery 5,6,7,8 Few earlier studies reported that there is significant cognitive impairment in patients with idiopathic GTCS without brain damage. 10,11 The cognitive impairment could be due to subtle brain damage which the present investigators could not exclude with neurological and neuropsychological investigations. The apparent cognitive impairment could be the result of impairment in concentration (BCRS).…”
Section: Discussionmentioning
confidence: 72%
“…37,38 Childhood onset absence epilepsy had subtle cognitive deficits and duration of illness, seizure frequency, antiepileptic drug treatment were related to the severity of the cognitive deficits. 11,39 Patients with idiopathic occipital lobe epilepsy scored worse than controls in intellectual functioning, memory, and attention. 40 Deficits in motor skills, response inhibition, attention, working memory, planning, and psychomotor speed were noted in patients with Temporal lobe epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with new-onset seizures or new-onset epilepsy are known to have neuropsychological deficits and academic underachievement, [23][24][25][26] even when they are intellectually healthy. It is possible that there is an antecedent neurobiologic alteration that predisposes to both seizures and neuropsychological deficits.…”
mentioning
confidence: 99%